Characterising the relationship between weather extremes in Europe and synoptic circulation features - S. Pfahl (Natural Hazards and Earth System Sciences, 2014)
Extreme weather events in Europe are closely linked to anomalies of the atmospheric circulation and in particular to circulation features like cyclones and atmospheric blocking. In this study, this linkage is systematically characterised with the help of conditional cyclone and blocking frequencies during precipitation, wind gust and temperature extremes at various locations in Europe. Such conditional frequency fields can serve as a dynamical fingerprint of the extreme events and yield insights into their most important physical driving mechanisms. Precipitation extremes over the ocean and over flat terrain are shown to be closely related to cyclones in the vicinity and the associated dynamical lifting. For extreme precipitation over complex terrain, cyclone anomalies are found at more remote locations, favouring the flow of moist air towards the topography. Wind gust extremes are associated with cyclone and blocking anomalies in opposite directions, with the cyclones occurring mostly over the North and Baltic seas for extreme events in central Europe. This setting is associated with pronounced surface pressure gradients and thus high near-surface wind velocities. Hot temperature extremes in northern and central Europe typically occur in the vicinity of a blocking anticyclone, where subsidence and radiative forcing are strong. Over southern Europe, blocking anomalies are shifted more to the north or northeast, indicating a more important role of warm air advection. Large-scale flow conditions for cold extremes are similar at many locations in Europe, with blocking anomalies over the North Atlantic and northern Europe and cyclone anomalies southeast of the cold extreme, both contributing to the advection of cold air masses. This characterisation of synoptic-scale forcing mechanisms can be helpful for better understanding and anticipating weather extremes and their long-term changes.